Tributaç\~ao e a Organizaç\~ao dos Prestadores de Serviços no Brasil - Silvia Helena Barcellos; Juliano J. Assunç\~ao (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2005)
– The real impact of taxes on the economy can only be assessed when we consider the behavioral responses of economic agents due to these taxes. This paper shows how income taxation in Brazil gives incentives to some classes of taxpayers to incorporate in order to reduce their tax burden. Microdata analysis on these taxpayers characteristics indicate that the probability of incorporation is strongly related to tax rule
Keywords: 330; Taxation; Organizational Form; Tax Avoidance.; Einkommensteuer; Steuerinzidenz; Steuervermeidung; Brasilien